Analyzing the Impact of Tax Policy on Financial Performance and Compliance of MSMEs in Indonesia - Sumiok, Cristofer (Sinergi International Journal of Accounting and Taxation, 2023)
The complex relationship between tax policy components and the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia is examined in this study. A survey was conducted with a sample of 250 MSMEs to capture different industry types, firm sizes, and geographical regions. The study assessed the relationship between tax rates, tax incentives, firm size, industry type, and financial performance indicators using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The structural model yielded important insights, while the measurement model demonstrated good validity and reliability. As lower profitability correlates with higher tax rates, policymakers should consider the tax burden of MSMEs. On the other hand, tax incentives show a good correlation with financial performance, suggesting that they may be useful in encouraging MSME expansion. The complex interaction between firm size industry type and financial performance is highlighted. The SEM-PLS model fits the data well, according to the model fit assessment. To support the sustainable expansion of MSMEs in Indonesia, policymakers and MSME owners can benefit from the results of this study, which has practical implications such as for the Government is the present policies need to be evaluated in order to improve MSME compliance. Meanwhile, it is important for MSMEs to improve their competencies such as financial literacy.